Evaluation of Stability of Charged Lithium-rich Layer-structured Cathode Material at Elevated Temperature. (1st July 2015) - Konishi, Hiroaki; Hirano, Tatsumi; Takamatsu, Daiko; Gunji, Akira; Feng, Xiaoliang; Furutsuki, Sho
Highlights: Stability of Li1.2(1- x ) Ni0.13 Mn0.54 Co0.13 O2 at high temperature was higher than that of Li1- y Ni0.8 Mn0.1 Co0.1 O2 . Oxidation state of Mn in Li1.2(1- x ) Ni0.13 Mn0.54 Co0.13 O2 was less changeable than those of Ni and Co. High stability of Li1.2(1- x ) Ni0.13 Mn0.54 Co0.13 O2 was attributed to high manganese content. Abstract: The stability of charged Li1.2 Ni0.13 Mn0.54 Co0.13 O2 at elevated temperature was investigated by using thermal desorption spectrometry-mass spectrometry (TDS-MS), X-ray diffraction (XRD), and X-ray absorption fine structure (XAFS) measurements. The TDS-MS and XRD spectra indicated that the crystal structure of the delithiated Li1.2 Ni0.13 Mn0.54 Co0.13 O2 changed from layer to spinel, and oxygen was released at high temperature. However, the amount of oxygen released from Li1.2 Ni0.13 Mn0.54 Co0.13 O2 in a full-charge state was much less than that released from LiNi0.8 Mn0.1 Co0.1 O2 in a full-charge state. The XAFS spectra indicated that the high oxidation state of manganese was more stable than that of nickel and cobalt. The high stability of charged Li1.2 Ni0.13 Mn0.54 Co0.13 O2 at high temperature was, therefore, attributed to the high manganese content of the transition metal.